2023
DOI: 10.3389/fpls.2023.1268448
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq provides insights into potato deubiquitinase responses to drought stress in seedling stage

Xun Tang,
Fujun Sun,
Ning Zhang
et al.

Abstract: Ubiquitination is a specific protein degradation and reversible post-translational modification process that can be reversed by deubiquitinase (DUBs). DUBs can hydrolyze and release ubiquitin in the substrate protein so that the substrate can avoid degradation or change its activity, and it has an impact on plant growth and development, cell cycle, abiotic stress response, and other biological processes. Transcript sequences of potato varieties “DM1-3”, “Atlantic” and “Cooperation-88” downloaded from Potato Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…More recently, Jian et al. (2022) and Tang et al. (2023) delved into the molecular responses of potatoes to drought stress and ubiquitination, respectively.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Jian et al. (2022) and Tang et al. (2023) delved into the molecular responses of potatoes to drought stress and ubiquitination, respectively.…”
Section: Modern Approaches For the Identification And Selection Of Re...mentioning
confidence: 99%
“…The study identified 5,508 DEGs and highlighted the significant enrichment of categories related to nucleic acid binding, transporter activity, ion/molecule transport, ion binding, kinase activity, and oxidative phosphorylation. More recently, Jian et al (2022) and Tang et al (2023) delved into the molecular responses of potatoes to drought stress and ubiquitination, respectively. Jian et al identified 12,798 DEGs in response to simulated drought stress, elucidating pathways such as galactose metabolism, fatty acid metabolism, and plant-pathogen interaction.…”
Section: Potatomentioning
confidence: 99%
“…Therefore, it is of great significance to study response mechanisms to physiological drought caused by osmotic stress and excavate differentially expressed genes of different crops. Relying on transcriptome sequencing approach, a large number of differentially expressed genes (DEGs) in response to Polyethylene Glycol (PEG) osmotic stress were identified [ 13 , 14 ]. In root and tuber crops, Karanja et al [ 15 ] reported that the RsERF045 , RsERF104 and RsERF184 genes were highly responsive to PEG in radish.…”
Section: Introductionmentioning
confidence: 99%